Identification of Secreted Exoproteome Fingerprints of Highly-Virulent and Non-Virulent Staphylococcus aureus Strains - Bonar, Emilia; Wojcik, Iwona; Jankowska, Urszula; Kedracka-Krok, Sylwia; Bukowski, Michal; Polakowska, Klaudia; Lis, Marcin W.; Kosecka-Strojek, Maja; Sabat, Artur J.; Dubin, Grzegorz; Friedrich, Alexander W.; Miedzobrodzki, Jacek; et al. (Frontiers in Cellular and Infection Microbiology, 2016)
Staphylococcus aureus is a commensal inhabitant of skin and mucous membranes in nose vestibule but also an important opportunistic pathogen of humans and livestock. The extracellular proteome as a whole constitutes its major virulence determinant; however, the involvement of particular proteins is still relatively poorly understood. In this study, we compared the extracellular proteomes of poultry-derived S. aureus strains exhibiting a virulent (VIR) and non-virulent (NVIR) phenotype in a chicken embryo experimental infection model with the aim to identify proteomic signatures associated with the particular phenotypes. Despite significant heterogeneity within the analyzed proteomes, we identified alpha-haemolysin and bifunctional autolysin as indicators of virulence, whereas glutamylendopeptidase production was characteristic for non-virulent strains. Staphopain C (StpC) was identified in both the VIR and NVIR proteomes and the latter fact contradicted previous findings suggesting its involvement in virulence. By supplementing NVIR, StpC-negative strains with StpC and comparing the virulence of parental and supplemented strains, we demonstrated that staphopain C alone does not affect staphylococcal virulence in a chicken embryo model.